THE ETHICS OF PRESCRIBING OFF-LABEL DRUGS IN CHILDREN. THE DILEMMA OF SILDENAFIL - Laszlo-Zoltan Sztankovszky; Magdalena Iorga; Cristian Gheonea; Georgiana Russu (Amaltea Medical Publishing House, 2015)
The off-label prescription means that medicines are administered by an unlicensed route, in an unlicensed formulation or dosage or to a child below the stated age range. The use of drugs in an off-label or unlicensed manner to treat children is widespread. Because many prescribed treatments for children have not been adequately tested in children, this population of patients remains a vulnerable one. On the one hand, prescribing off-label use drugs in children determines a lot of controversies but, one the other hand, without this possibility, could be deprived of a chance to be treated. The paper presents the widespread phenomenon of off-label us drugs in children, refl ecting in scientifi c studies in USA and Europe. An important focus is on Romanian statistic of Sildenafi l prescription and on dilemmatic use of it in pediatric cardiology unit.